Upaya Hukum Penghapusan Diskriminasi dan Rasisme Terhadap Masyarakat Asli Papua - Hendrian Bagus Berlianto (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Today, the world is full with issues of discrimination and racism against blacks. Many Indonesia citizen supported and filled out petitions entitled “Blacklivesmatter” to help those issues that were taking place in America. However, unwittingly in Indonesia itself there is still much discrimination and racism against the Papuans. Papuans themselves have long experienced discrimination and racism behaviors in Indonesia, ranging from race, skin color, culture, ethnicity, to way of thinking or lifestyle. Whereas in Indonesia itself there are already regulations that overwhelm the discrimination and racism contained in the Number 40 Act of 2008 on the abolition of Race and Ethnic discrimination. Therefore, it needs to take reviews and analysis of how the legal role and role of Indonesian citizens themselves are in flattening the rights of Papuans in coexisting and equal.